Risk Perceptions of Airbnb Hosts: Evidence from a Mediterranean Island - Malazizi, Nahid; Alipour, Habib; Olya, Hossein (Mdpi, 2018)
In the context of the sharing economy, Airbnb has become a formidable mode of accommodation in the tourism industry worldwide, with a presence in over 34,000 cities in 191 countries. However, the risks associated with online bookings are significant dimensions of this e-market domain. This study assesses Airbnb hosts' perceived risks and investigates the effects of service, financial, safety and security, psychological and political risks on the host's satisfaction and intention to continue and recommend this business to potential hosts. A survey was administered to 221 Airbnb hosts located in Northern Cyprus. Structural equation modeling (SEM) was used to test the proposed conceptual model. The results revealed that host satisfaction is negatively influenced by financial and safety and security risks; continuance intention is negatively affected by financial, safety and security, and political risks; intention to recommend this business is negatively affected by political risk; and psychological risk increases satisfaction and intention to continue and recommend. By highlighting the theoretical and managerial implications, this study informs Airbnb management of the potential risks associated with this peer-to-peer (P2P) business in order to minimize the associated risks, enhance host satisfaction and the quality of their services, and encourage hosts to recommend Airbnb to their peers.
Keywords: Airbnb; risk; host; sharing economy; psychological risk; peer-to-peer business